BIOELECTRIC POTENTIAL MEASUREMENT OF ORAL CAVITY OF DENTAL PATIENTS - E. E. Vasenev; I. F. Alechanova; I. V. Starikova; T. N. Radyshevskaya (Медицинский вестник Юга России, 2016)
Purpose: 39 patients were conducted 156 measurements of bioelectric potential of the oral mucosa.Materials and Methods: all examined patients have different metallic inclusions. The control group consisted of 20 patients (aged 41-67 years old) with diseases of hard dental tissues (caries and its complications).Results: the patients with galvanism were received oral cavity sanation which included the removal of dissimilar metals from oral cavity and the antiinflammatory treatment of paradentium.Summary: the elimination of local factors doesn’t reduce the values of bioelectric potential (BP) up to the physiological norm. After the completion of treatment the values of BP have decreased on average by 20%.